A new species of Zitha Walker, 1866 and three new records of pyraloid moths (Insecta, Lepidoptera) from India - Irungbam, Jatishwor Singh; Mally, Richard (Zootaxa, 2025)
Zitha ferrugineofasciata Irungbam & Mally sp. nov. (Pyralidae: Pyralinae) is described based on 12 male adult specimens collected in Manipur state, India. In addition, three species, Circobotys obscuriptera Wang, 2018 (Crambidae: Pyraustinae), Neoanalthes nebulalis Yamanaka & Kirpichnikova, 1993 (Crambidae: Spilomelinae) and Teliphasa spinosa Li, 2016 (Pyralidae: Epipaschiinae) are reported from India for the first time. Illustrations of the adults and their genitalia are provided.